2014
DOI: 10.1121/1.4877313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and improvement of a model to predict the measurement uncertainty due to the directivity of room acoustical sound sources

Abstract: With the aim to reduce the necessary efforts to empirically determine the uncertainty in room acoustical measurements, in previous work, a model was developed that can predict the uncertainty a directivity of a sound source introduces to a measurement. As part of the validation extensive series of scale measurements have been conducted. In this contribution, the predicted uncertainty based on simulations and the empiric data is compared to each other. The results were used to improve the model. Concluding it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Today the measurement procedure can be considered generally accepted and research discusses different influences and their effect on the uncertainty. Among other influences investigations target the directivity of sound sources (Knüttel, Witew, & Vorländer, 2013;Leishman, Rollins, & Smith, 2006;San Martin, Witew, Arana, & Vorländer, 2007;Witew, Knüttel, & Vorländer, 2012;Witew, Müller-Giebeler, & Vorländer, 2014), the directivity of receivers (Witew & Behler, 2003;Witew, Lindau, et al, 2013), the position of the receiver (de Vries et al, 2001;Witew, Behler, & Vorländer, 2004;Witew & Vorländer, 2011) but also the algorithm to analyse impulse responses (Guski & Vorländer, 2015;Katz, 2004;Witew & Behler, 2005). This multitude of individual studies makes it difficult to reach an aggregate perspective and thus to distinguish significant from more moderate influences.…”
Section: Previous Workmentioning
confidence: 99%
“…Today the measurement procedure can be considered generally accepted and research discusses different influences and their effect on the uncertainty. Among other influences investigations target the directivity of sound sources (Knüttel, Witew, & Vorländer, 2013;Leishman, Rollins, & Smith, 2006;San Martin, Witew, Arana, & Vorländer, 2007;Witew, Knüttel, & Vorländer, 2012;Witew, Müller-Giebeler, & Vorländer, 2014), the directivity of receivers (Witew & Behler, 2003;Witew, Lindau, et al, 2013), the position of the receiver (de Vries et al, 2001;Witew, Behler, & Vorländer, 2004;Witew & Vorländer, 2011) but also the algorithm to analyse impulse responses (Guski & Vorländer, 2015;Katz, 2004;Witew & Behler, 2005). This multitude of individual studies makes it difficult to reach an aggregate perspective and thus to distinguish significant from more moderate influences.…”
Section: Previous Workmentioning
confidence: 99%
“…Today the measurement procedure can be considered generally accepted and research discusses different influences and their effect on the uncertainty. Among other influences investigations target the directivity of sound sources (Knüttel, Witew, & Vorländer, 2013;Leishman, Rollins, & Smith, 2006;San Martin, Witew, Arana, & Vorländer, 2007;Witew, Knuettel, & Vorländer, 2012;Witew, Müller-Giebeler, & Vorländer, 2014), the directivity of receivers (Witew & Behler, 2003;Witew, Lindau, et al, 2013), the position of the receiver (de Vries et al, 2001;Witew, Behler, & Vorländer, 2004; but also the algorithm to analyze impulse responses (Guski & Vorländer, 2015;Katz, 2004;Witew & Behler, 2005).…”
Section: Reproducibility Conditionmentioning
confidence: 99%
“…The implied model suggests a constant uncertainty contribution over the running time of the impulse response. Using a very large data collection, Witew et al (2014) have shown that the uncertainty of the impulse response due to the source's directivity changes over the running time of the impulse response. The very early parts of the impulse response show a significantly higher uncertainty compared to the later parts of the (diffuse) exponential decay.…”
Section: Electroacoustic Sound Sourcesmentioning
confidence: 99%
See 1 more Smart Citation